Internet Delivered Support for Tobacco Control in Dental Practice: Randomized Controlled Trial - Houston, Thomas K; Richman, Joshua S; Ray, Midge N; Allison, Jeroan J; Gilbert, Gregg H; Shewchuk, Richard M; Kohler, Connie L; Kiefe, Catarina I (JMIR Publications, 2008)
Background The dental visit is a unique opportunity for tobacco control. Despite evidence of effectiveness in dental settings, brief provider-delivered cessation advice is underutilized. Objective To evaluate an Internet-delivered intervention designed to increase implementation of brief provider advice for tobacco cessation in dental practice settings. Methods Dental practices (N = 190) were randomized to the intervention website or wait-list control. Pre-intervention and after 8 months of follow-up, each practice distributed exit cards (brief patient surveys assessing provider performance, completed immediately after the dental visit) to 100 patients. Based on these exit cards, we assessed: whether patients were asked about tobacco use (ASK) and, among tobacco users, whether they were advised to quit tobacco (ADVISE). All intervention practices with follow-up exit card data were analyzed as randomized regardless of whether they participated in the Internet-delivered intervention. Results Of the 190 practices randomized, 143 (75%) dental practices provided follow-up data. Intervention practices' mean performance improved post-intervention by 4% on ASK (29% baseline, adjusted odds ratio = 1.29 [95% CI 1.17-1.42]), and by 11% on ADVISE (44% baseline, OR = 1.55 [95% CI 1.28-1.87]). Control practices improved by 3% on ASK (Adj. OR 1.18 [95% CI 1.07-1.29]) and did not significantly improve in ADVISE. A significant group-by-time interaction effect indicated that intervention practices improved more over the study period than control practices for ADVISE (P = 0.042) but not for ASK. Conclusion This low-intensity, easily disseminated intervention was successful in improving provider performance on advice to quit. Trial Registrationclinicaltrials.gov NCT00627185; http://clinicaltrials.gov/ct2/show/NCT00627185 (Archived by WebCite at http://www.webcitation.org/5c5Kugvzj)